Intravenous pulses of methylprednisolone for infants with severe bronchopulmonary dysplasia and respiratory support after 3 months of age. Issue 1 (19th October 2020) - Billion, Elodie; Hadchouel, Alice; Garcelon, Nicolas; Delacourt, Christophe; Drummond, David
Abstract: Introduction: There are few published data on the efficacy of systemic corticosteroids in preterm infants with very severe forms of bronchopulmonary dysplasia (BPD), requiring respiratory support after 3 months of age. The aim of this study was to report the use of pulses of methylprednisolone in this population and its consequences on the level of respiratory support. Methods: This retrospective monocentre study included infants over 3 months of age with severe BPD who received at least one pulse of methylprednisolone (300 mg/m 2 /day intravenous [IV] over 3 days). The primary outcome was the evolution of the pulmonary severity score (PSS) during the 3 months preceding and the 5 months following the first pulse. The evolution of the median PSS over time was analyzed using linear segmented regression for interrupted time series. Results: Ten infants were included. During the 3 months preceding the first pulse, a significant increase in the median PSS was observed ( p  = .01), followed by a progressive decrease during the 5 months after administration of the first pulse ( p  < .01). Greater effects were observed in more severe infants requiring mechanical or noninvasive ventilation than in those receiving supplemental oxygen through nasal cannula. Conclusion: High‐dose IV pulses of methylprednisolone were associated with a decrease in the level of respiratory support required by infants with very severe forms of BPD, with a greater effect in those on mechanical or noninvasive ventilation. Further studies are warranted to confirm these preliminary results and assess the long‐term safety of this therapy.